Enhanced aerobic exercise performance in women by a combination of three mineral Chelates plus two conditionally essential nutrients - Robert A. DiSilvestro; Staci Hart; Trisha Marshall; Elizabeth Joseph; Alyssa Reau; Carmen B. Swain; Jason Diehl (Taylor & Francis Group, 2017)
Background Certain essential and conditionally essential nutrients (CENs) perform functions involved in aerobic exercise performance. However, increased intake of such nutrient combinations has not actually been shown to improve such performance. Methods For 1 mo, aerobically fit, young adult women took either a combination of 3 mineral glycinate complexes (daily dose: 36 mg iron, 15 mg zinc, and 2 mg copper) + 2 CENs (daily dose: 2 g carnitine and 400 mg phosphatidylserine), or the same combination with generic mineral complexes, or placebo (n = 14/group). In Trial 1, before and after 1 mo, subjects were tested for 3 mile run time (primary outcome), followed by distance covered in 25 min on a stationary bike (secondary outcome), followed by a 90 s step test (secondary outcome). To test reproducibility of the run results, and to examine a lower dose of carnitine, a second trial was done. New subjects took either mineral glycinates + CENs (1 g carnitine) or placebo (n = 17/group); subjects were tested for pre- and post-treatment 3 mile run time (primary outcome). Results In Trial 1, the mineral glycinates + CENs decreased 3 mile run time (25.6 ± 2.4 vs 26.5 ± 2.3 min, p < 0.05, paired t-test) increased stationary bike distance after 25 min (6.5 ± 0.6 vs 6.0 ± 0.8 miles, p < 0.05, paired t-test), and increased steps in the step test (43.8 ± 4.8 vs 40.3 ± 6.4 steps, p < 0.05, paired t-test). The placebo significantly affected only the biking distance, but it was less than for the glycinates-CENs treatment (0.2 ± 0.4. vs 0.5 ± 0.1 miles, p < 0.05, ANOVA + Tukey). The generic minerals + CENs only significantly affected the step test (44.1 ± 5.2 vs 41.0 ± 5.9 steps, p < 0.05, paired t-test) In Trial 2, 3 mile run time was decreased for the mineral glycinates + CENs (23.9 ± 3.1 vs 24.7 ± 2.5, p < 0.005, paired t-test), but not by the placebo. All changes for Test Formula II or III were high compared to placebo (1.9 to 4.9, Cohen's D), and high for Test Formula II vs I for running and biking (3.2 & 3.5, Cohen's D). Conclusion In summary, a combination of certain mineral complexes plus two CENs improved aerobic exercise performance in fit young adult women.